Assessing Capability in Design and Technology: The case for a minimally invasive approach - Barlex, David (Design and Technology Education: An International Journal, 2007)
The approach to assessing capability in design and technology advocated requires four features. First, there is the requirement for tasks that are culturally and personally authentic through which pupils can demonstrate designerly behaviour by making design decisions. Second, there is the requirement that the pupils use job bags, whose contents are based on utility, as the means of making and recording their design decisions. Third there is the requirement that scripted probes are used at key points in the design task to enable pupils to divulge and record their designerly thinking through revealing and justifying their design decisions. Fourth, it requires teachers to play the part of mentor and client in helping pupils use the scripted probes effectively. The paper is in seven parts. Part 1 briefly explores the difficulties in defining designerly activity. Part 2 considers some of the problems in revealing designerly activity. Part 3 considers the nature of tasks that might be appropriate for assessment in design and technology. Part 4 considers how designing might be describes as a set of interrelated design decisions. Part 5 describes how such design decisions might be revealed and justified through the use of a series of scripted probes. Part 6 considers the nature of the portfolio that enables pupils to make design decisions. In the conclusion, the paper summarises the approach to assessment developed so far and justifies it in terms of overcoming the problems of revealing designerly activity and having minimum impact on the pupils experience of designing. While most of the examples in this paper are drawn from the specific context of assessment in England and Wales, the ideas and issues raised and discussed will have relevance for all concerned with developing authentic approaches to assessment in Technology Education.